2011
DOI: 10.1016/j.cell.2011.11.029
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of PKR Promotes Network Excitability and Enhanced Cognition by Interferon-γ-Mediated Disinhibition

Abstract: SUMMARY The double-stranded RNA-activated protein kinase (PKR) was originally identified as a sensor of virus infection, but its function in the brain remains unknown. Here, we report that the lack of PKR enhances learning and memory in several behavioral tasks while increasing network excitability. In addition, loss of PKR increases the late phase of long-lasting synaptic potentiation (L-LTP) in hippocampal slices. These effects are caused by an interferon-γ (IFN-γ)-mediated selective reduction in GABAergic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
160
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 184 publications
(180 citation statements)
references
References 62 publications
13
160
2
Order By: Relevance
“…Whereas it remains unknown whether the principles described for the VTA also apply to the hippocampus, we speculate that ISRIB enhances cognitive abilities by blocking LTD and consequently enhancing LTP, thus keeping synaptic connections stronger. Indeed, reduction of eIF2α phosphorylation enhances hippocampal LTP (19,22), but blocks mGluR-LTD (33). By contrast, induction of eIF2α phosphorylation in hippocampal neurons impairs LTP (19,25) and induces mGluR-LTD (33).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Whereas it remains unknown whether the principles described for the VTA also apply to the hippocampus, we speculate that ISRIB enhances cognitive abilities by blocking LTD and consequently enhancing LTP, thus keeping synaptic connections stronger. Indeed, reduction of eIF2α phosphorylation enhances hippocampal LTP (19,22), but blocks mGluR-LTD (33). By contrast, induction of eIF2α phosphorylation in hippocampal neurons impairs LTP (19,25) and induces mGluR-LTD (33).…”
Section: Discussionmentioning
confidence: 97%
“…Electrophysiological recordings were performed as previously described (22,72,73). Briefly, hippocampal slices (350 μm) were cut from brains of sham and TBI (focal injury; n = 7-9 per group) mice in 4°C artificial cerebrospinal fluid (ACSF), kept in ACSF at room temperature for at least 1 hr before recording, and maintained in an interface-type chamber perfused with oxygenated ACSF (95% O 2 and 5% CO 2 ) containing in millimoles: 124 NaCl, 2.0 KCl, 1.3 MgSO 4 , 2.5 CaCl 2 , 1.2 KH 2 PO 4 , 25 NaHCO 3 , and 10 glucose (2-3 mL/min).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was shown that reduction of eIF2a phosphorylation in mice lacking the eIF2a kinase general control nonderepressible 2 (GCN2) and in heterozygous knockin mice with a mutation on serine 51 of eIF2a results in a lowered threshold for inducing long-lasting late-phase long-term potentiation (L-LTP) (Costa-Mattioli et al 2005. In addition, mice harboring a deletion of the double-stranded (ds) RNA-activated protein kinase (PKR) show a similar decrease in threshold for inducing L-LTP (Zhu et al 2011). Conversely, increased eIF2a phosphorylation in transgenic mice overexpressing PKR causes increased expression of ATF4 and impaired L-LTP (Jiang et al 2010).…”
mentioning
confidence: 99%
“…However, in some cases, it is clear that the gene causing the epileptic phenotype is also partially or totally responsible for the cognitive impairment (Bender et al 2013). Indeed, in some single-gene models, there is evidence that a gain in cognitive function may coexist with epilepsy, suggesting that seizures are not always destructive and that the pathways for cognition and epilepsy can occasionally be dissected (Zhu et al 2011).…”
Section: Epileptic Encephalopathiesmentioning
confidence: 99%